Heritage. Human rights and memory in Chile. Rating sites as cultural memory - Alegría, Luis (2018)
The emergence of a new category of assets linked to the experience of the systematic and massive violations of human rights, is one of the unexpected consequences of the implementation of the strategy of state terrorism in Chile. These physical marks of the last military dictatorship (1973-1990), have been expressed in the descriptions of atrocity or horror with which recount process and socially, we argue that for that to be possible, it was necessary to make themselves three key processes. First, the finding of extreme experience representing Nazi extermination policy and universal value, two, as a direct effect of the above, the creation of a human rights culture of a planetary, and three, the expansion of the traditional conception of cultural heritage. Only the combination of these three phenomena, it is possible today to identify sites of memory as a set of assets.